New troglobitic and troglophilic syntopic species of Endecous (Orthoptera, Grylloidea, Phalangopsidae) from a Brazilian cave: a case of sympatric speciation? - Castro-Souza, Rodrigo Antônio; Zefa, Edison; Ferreira, Rodrigo Lopes (Zootaxa, 2020)
Crickets of the genus Endecous (Orthoptera: Grylloidea: Phalangopsidae) are frequently found in caves, in some cases presenting strictly subterranean lifestyle. In addition to the morphological diagnostic characters of the group, bioacoustic and karyotype, also help on delimiting species. Here, we describe two new sympatric species of this genus, which occur in the largest cave of Minas Gerais state, Brazil, using the morphology of phallic complex, the courtship song and karyotype. Moreover, we discuss the criteria used, the troglomorphisms for this genus, as well as hypothesis on the speciation process involving these species.